Komunikasi Interpersonal Mahasiswa Laki-Laki Kepada Orang Tua Di Stisip Widyapuri Mandiri Sukabumi - Fitri Annisa Rachmah; Fitri Natalia (Jurnalika : Jurnal Ilmu Komunikasi, 2023)
This study describes the lack of communication between children and parents based on the results of a survey of male students at STISIP Widyapuri Mandiri Sukabumi. The purpose of this study was to identify aspects of Interpersonal Communication related to the relationship between boys and parents, focusing on openness, empathy, supportive attitude, positive attitude, and equality. A qualitative approach with phenomenological method was used, involving 6 informants: 4 male students from different study programs and 2 parents. Data were collected through interviews, observations, and recordings, and validated using triangulation. The results show that Interpersonal Communication between boys and parents is not optimal, especially in terms of openness and equality. However, empathy and positive attitudes in Interpersonal Communication are still maintained. This study illustrates that although some aspects of communication need improvement, there are positive elements in the interaction between boys and parents in STISIP Widyapuri Mandiri Sukabumi.